Bacterial profile and their antibiotic resistance in an ICU of Bangladesh: Comparison of four studies from 2004 to 2011 - Fatema, Kaniz; Ahsan, ASM Areef; Barai, Lovely; Ahmed, Fatema; Haq, Jalaluddin Ashraful; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2016)
Antimicrobial resistance plays a vital role in determining the outcome of the critically ill patients with infections in intensive care unit (ICU). Aim: The objective of this study was to evaluate the frequencies of isolated pathogens and their resistance pattern in an ICU of Bangladesh. The study also aimed to analyze and compare the trends of bacterial population and their resistance pattern in the same ICU between 2004 and 2011 in four different studies. Materials and Method: A cross sectional study was carried out in a 10 bed adult ICU of a tertiary care hospital of Bangladesh over a period of 10-month, from January 2011 to October 2011. Blood, respiratory secretions and urine from patients with clinically suspected infections were included in the study. Findings were compared with previous three studies done in 2004, 20006-07, and 2008-09 in same ICU. Results: In 2011, a total of 1408 samples were analyzed. Six hundred eighty-four micro-organisms were isolated from 597 samples. Maximum growth was obtained from respiratory secretions (71.7%). Organisms isolated were Acinetobacter sp. (46.4%), Pseudomonas sp. (21.4%), Candida sp. (11.5%), Klebsiella sp. (9.9%), Eschericia coli (4.1%) and Staphylococcus aureus (2.9%). Major gram negative organisms were highly resistant to 3rd generation cephalosporins (>70%). All Acinetobacter sp. were extremely resistant (>85%) to all antibiotics except colistin. Resistance of isolated Pseudomonas sp. was >65% to ciprofloxacin, >70% to aminoglycosides, and >85% to imipenem. About 72% of the isolated Staphylococcus aureus was methicillin resistant with variable resistant to other antibiotics. Comparing the findings of this study with previous three studies done in same ICU, it has been found that rate of isolation of Acinetobacter sp., was increased significantly (p<0.05) in this ICU population with decrease in rate of Pseudomonas sp., Eschericia coli, Staphylococcus aureus, Enterococci sp., and Candida sp. Resistances pattern of two commonest gram negative organisms, eg Acinetobacter sp. and Pseudomonas sp., to the available antibiotics showed gradual increase in resistance from 2004 to 2011. Conclusion: It is recommended that strict infection control policies and antibiotic stewardship program must be implemented to solve this emerging drug resistance problem which might cause high morbidity and mortality in ICU patients. Bangladesh Crit Care J September 2016; 4 (2): 79-85